2020
DOI: 10.3390/genes11121402
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Mapping of a Wild Genomic Region Involved in Pod and Seed Size Reduction on Chromosome A07 in Peanut (Arachis hypogaea L.)

Abstract: Fruit and seed size are important yield component traits that have been selected during crop domestication. In previous studies, Advanced Backcross Quantitative Trait Loci (AB-QTL) and Chromosome Segment Substitution Line (CSSL) populations were developed in peanut by crossing the cultivated variety Fleur11 and a synthetic wild allotetraploid (Arachis. ipaensis × Arachis. duranensis)4x. In the AB-QTL population, a major QTL for pod and seed size was detected in a ~5 Mb interval in the proximal region of chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 65 publications
1
26
0
Order By: Relevance
“…Several major quantitative trait loci (QTLs) related to peanut pod size have been reported in recent years ( Huang et al, 2015 ; Chen et al, 2016 ; Luo et al, 2017 ; Luo et al, 2018 ; Alyr et al, 2020 ; Chu et al, 2020 ; Gangurde et al, 2020 ). Luo et al (2017) identified three major QTLs for hundred-pod weight (HPW), pod length and width (PL and PW), which were co-localized in the same region on chromosome A05.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several major quantitative trait loci (QTLs) related to peanut pod size have been reported in recent years ( Huang et al, 2015 ; Chen et al, 2016 ; Luo et al, 2017 ; Luo et al, 2018 ; Alyr et al, 2020 ; Chu et al, 2020 ; Gangurde et al, 2020 ). Luo et al (2017) identified three major QTLs for hundred-pod weight (HPW), pod length and width (PL and PW), which were co-localized in the same region on chromosome A05.…”
Section: Introductionmentioning
confidence: 99%
“… Chu et al (2020) identified one major QTL for pod-related traits in a 9 Mbp interval on linkage group A05. Alyr et al (2020) identified one QTL associated with pod and seed size in a 168.37 kb interval on chromosome A07. Gangurde et al (2020) identified 44 major effect QTLs related to PW and SW in two nested-association mapping populations, and found that most of the QTLs distributed on chromosomes A05, A06, B05, and B06.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, as the demand for oil is ever-increasing, there is an urgent need to breed new peanut varieties with high yields, a characteristic that is dependent on seed size. Several major quantitative trait loci (QTLs) related to peanut pod size have been obtained in recent years [ 12 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Luo and colleagues found three major consistent and stable QTLs for pod size and weight, which were co-localized in a 3.7 cm interval on chromosome A05 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two genes were predicted in this region, with two genes of interest, Aradu.RLZ61 and Aradu.DN3DB, encoding a transcriptional regulator, an F-box SNEEZY (SNE), and STERILE APETALA-like (SAP), respectively. These genes play a critical role in regulating seed and fruit size [ 67 ]. Moreover, MINI SEED 2 ( MIS2 ) regulates grain size by coordinately controlling epidermal cell number and cell size, and microscopic analysis showed that mis2 mutant rice revealed reduced cell size of spikelet epidermis but higher cell numbers [ 54 ].…”
Section: Genetic Factors Controlling Seed Sizementioning
confidence: 99%